Motivating the industrial sales force in the sales forecasting process - McCarthy Byrne, Teresa M. (Henry Stewart Talks, 2010)
Sales Force Motivational Theories, Discussion of 1000 depth interviews related to sales force forecasting, Results of survey of sales force forecasting, Identification of environmental signals that motivate sales force forecasting, Recommended approaches for managers to improve sales force performance in the forecasting process.